Tinjauan Ideologis dan Hubungan Ekonomi Islam Dengan Ekonomi Pancasila - Ahmad Farikhin LC., ME (Perbanas Journal of Islamic Economics and Business, 2022)
Economics, like other activities, has an ideological basis as a foothold and a source of inspiration for the perpetrators. Islam is here to provide solutions for people's lives in the economic field with the principles of justice and balance based on the revelation of God Almighty. Meanwhile, Pancasila as the foundation of the state ideology is also an inspiration in carrying out the economic activities of the Indonesian nation. This study explores the ideological correlation between the economic concept in Islam and the economic concept in Pancasila. Can the two economic concepts grow and develop hand in hand in Indonesia, which is based on Pancasila? This research is a quantitative research with a literature approach which is then described in the form of a narrative to explain the analysis and findings. In this study, it was found that the concept of Islamic economics is in line with the economic concept of Pancasila, considering that the precepts in Pancasila are also inspired by Islamic religious beliefs such as the concept of divinity (tawhid), humanity and justice. Islamic economy can grow and develop in Indonesia without changing the state system with the caliphate.